LATAR BELAKANG MUNCULNYA ILMU BALAGHAH, TOKOH-TOKOH, KARYA-KARYANYADAN ASPEK-ASPEKNYA - Abdul Wahab Syakhrani; Saipul Rahli (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Before emerging as a science, the essence of balaghah had been ingrained in the use of Arabic in both poetry and prose. During this period, the Al-Quran came down with miracles so that it beat others in terms of the accuracy and beauty of its language. The science of balaghah with its three divisions began to appear and be known during the second abbasiy period, namely the third and fourth centuries of the hijriyah. At this time, the balaghah was still unclear. This appearance was accompanied by the compilation of a book with that theme. Then, this science developed starting in the fifth century with its characteristics that began to intersect with I'jazul Quran, giving rise to two schools of balaghah, namely the flow of literature and kalam. The two differ in their perspective on the balaghah. The balaghah- kalam school relies more on analogy and philosophical logic in measuring whether language is good or not, while the literary school emphasizes artistic power and the ability to perceive beauty. The science of balaghah which continues to develop and reaches us today is one that is more in a kalamiyyah style, has many word boundaries and definitions